Экологически чистые холоднотвердеющие смеси на олигофурфурилоксисилаксановых связующих для литейных форм и стержней - Евтушенко, Наталья Сергеевна; Пономаренко, Ольга Ивановна (Wydawnictwo Wydziału Inżynierii Produkcji i Technologii Materiałów Politechniki Częstochowskiej, 2017)
The article presents to use ecologically pure bindings for of cold-solidifying mixtures preserving the indices of their basic physical and mechanical and technological properties to produce quality castings made of cast iron, steel and non-ferrous metals.
Ecologically pure cold-solidifying mixtures for molds and cores on oligofurfuralxylaxane bindings
Keywords: ХТС; термодеструкция; синтетические смолы; ОФОС